2015
DOI: 10.1111/ppl.12363
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of fine root respiration to soil warming involves starch deposition in very fine and fine roots: a case study in Fagus sylvatica saplings

Abstract: Root activities in terms of respiration and non-structural carbohydrates (NSC) storage and mobilization have been suggested as major physiological roles in fine root lifespan. As more frequent heat waves and drought periods within the next decades are expected, to what extent does thermal acclimation in fine roots represent a mechanism to cope with such upcoming climatic conditions? In this study, the possible changes in very fine (diameter < 0.5 mm) and fine (0.5-1 mm) root morphology and physiology in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 72 publications
(105 reference statements)
1
23
1
Order By: Relevance
“…3), with all responses being driven mainly by the enhanced formation of #0.5 mm roots. These results suggest that AP-treated seedlings of P. orientalis might possess a greater ability to adapt to increased competition and exploit belowground resources (Di Iorio et al, 2016;Perrig et al, 2007). In parallel, we only observed a significant increase in RL, RT, RSA, and SRL of 0.5-to 1-mm roots after AP on the 190th day, thus associating it to the long-term effect of AP.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…3), with all responses being driven mainly by the enhanced formation of #0.5 mm roots. These results suggest that AP-treated seedlings of P. orientalis might possess a greater ability to adapt to increased competition and exploit belowground resources (Di Iorio et al, 2016;Perrig et al, 2007). In parallel, we only observed a significant increase in RL, RT, RSA, and SRL of 0.5-to 1-mm roots after AP on the 190th day, thus associating it to the long-term effect of AP.…”
Section: Discussionsupporting
confidence: 61%
“…Fine roots, especially #0.5-mm roots, perform important physiological functions in terms of water and nutrient uptake Perrig et al, 2007). Some investigators have also found that fine roots are involved in the synthesis of certain growth hormones and associated with root adaptations for survival in changing environments (Di Iorio et al, 2016;Makita et al, 2016;Mosca et al, 2017). We found that the fine roots (#0.5 mm) of P. orientalis seedlings under AP had significantly higher RL, RT, RSA, and SRL (except for 120 d) compared with NP at 120, 150, and 190 d (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This would be considered a form of acclimation. Similarly, Di Iorio, Giacomuzzi, and Chiatante () found that European beach ( Fagus sylvatica ) has the ability to increase concentrations of starch in the fine roots as a “carbon‐savings strategy,” and in tomato ( Solanum lycopersicum ), decreases in proteins associated with nutrient‐uptake and assimilation have occurred in response to heat‐stress levels of temperature (Giri, Heckathorn, Mishra, & Krause, ).…”
Section: Introductionmentioning
confidence: 99%
“…Root orders along the branching hierarchy of roots < 2 mm in diameter encompass a diversity of forms and functions (Long et al 2013;Iversen et al 2017). In various studies with different species, fine root traits such as respiration (Di Iorio et al 2015), production, lifespan, and decomposition rate (Gill and Jackson 2000;Guo et al 2008, McCormack et al 2012Sun et al 2013;Van Do et al 2016), carbon, starch, and nitrogen concentration (Terzaghi et al 2013(Terzaghi et al , 2016, and relationship with soil temperature and water content (Montagnoli et al 2012a(Montagnoli et al , 2014 vary seasonally. Moreover, this seasonal fine root growth is of different magnitude and type (i.e., longitudinal and radial) depending on the diameter class considered.…”
Section: Introductionmentioning
confidence: 99%